ISLAMIC BANKING SYSTEM IN THE SULTANATE OF OMAN FROM THE PERSPECTIVE OF BANKING OFFICERS EMPLOYEES AND CUSTOMERS - Bulushi, Sultan Khamis Said Al (International Journal of Islamic Banking and Finance Research, 2021)
This research aims to determine the viability for the operation of Islamic banks within the Omani banking system. By looking into various opportunities for Islamic banking in Oman and given the unique rules on transactions (ﬁqh muamalat) of Islamic banking based on the Shariah precepts or the so-called Islamic law. As the establishment of small and medium enterprises (SMEs) is rapidly growing in Oman, many SMEs can draw support from Islamic banks. The study used a mixed method approach to answer the research questions. Do the participants patronize Islamic banking over conventional banking?. The study compared both conventional and Islamic Banking. The population of the study represented bank officers, bank employees and customers. The sample of the study (n=100) participated in the survey. Another selected sample participated in interviews. Findings revealed different views over Islamic banking. Islamic banking is careful to provide products and services. Also, they are found to be capable of offering products and processes that answers the need of certain aspects with a risk management framework that is distinct from what normal banking provides. The study findings support the need for Islamic banking systems as it would be easier to spread Islamic banking and financing. JEL Classification Codes: E5, E58, G2, G21, E4, E42.